Idioms in L2 English Essays by Swedish University Students : Idiom Types and The Effect of Spending Time in an English-speaking Environment - Vuorinen, Tomi (My University, 2022)
The topic of the thesis is English idioms in essays written by Swedish university students and the effect of spending time in an English-speaking environment has on their idiom usage. The material of the study is collected from The Uppsala Student English Corpus (USE) which is available online. 50 texts were collected from the corpus: 25 from students with 0 to 6 months of experience and 25 from students with more than 6 months of experience. The essays were read and checked for idiomatic expressions while also marking down the form of the idiom. The three forms of idioms were literal, semi-literal and pure idioms, based on idiom classification by Fernando (1996). The study is exploratory in a quantitative manner. The main results are that the group with over 6 months of experience used more idioms, but when examining the relationship between the amount of experience reported as months, no link between higher numbers of months of experience and more idiom usage was found. In fact, more months of experience seemed to lead to less idiom usage. The conclusion is that over 6 months of experience in English-speaking environment has a positive effect on idiom use but there might be a threshold after which the effect diminishes. The suggestion is that this material should be examined more closely with quantitative methods using a higher number of essays.
Keywords: idioms, formulaic language, vocabulary